Unknown movie scripts by Yevgeny Zamyatin - Alexander Stroev (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The publication of four unknown movie scripts by Yevgeny Zamyatin 1934–1936, stored in France: “Bich Bozhii» (revised script of his play “Attila”), “Vladyka Azii” (modified and expanded version of the script “Genghis Khan”), “Ivan Groznyi” and “Princess Vanina” (a staging of the novel by Stendhal). The introductory article analyzes Zamyatin’s scripts both in the context of the writer's work and the literature of the Silver Age. They are built on constant leitmotivs (Kiss / Poison, Love / Fight, Passion / Power) and can be considered a single text. At the center of events is a strong Woman, conquering weak men and entering in confrontation with the Archon. The plot takes on the form of a “serpent myth” in which a woman — a tempting snake — forces a riot, brings death to the sovereign. Behind the love conflict of Zamyatin's scripts are the historiosophical concepts of the writer, political allusions, and a number of mystical motives.